Role of Genes in Regulating Host Plants Expansion in Tephritid Fruit Flies (Diptera) and Potential for RNAi-Based Control. Issue 4 (19th August 2022) - Shi, Wei; Ye, Hui; Roderick, George; Cao, Jun; Kerdelhué, Carole; Han, Peng
Abstract: Host plant expansion is an important survival strategy for tephritids as they expand their range. Successful host expansion requires tephritids to adapt to the chemical and nonchemical properties of a novel host fruit, such as fruit color, phenology, and phytochemicals. These plant properties trigger a series of processes in tephritids, with each process having its own genetic basis, which means that various genes are involved in regulating host plant expansion by tephritids. This review summarizes current knowledge on the categories and roles of genes involved in host plant expansion in several important tephritid species, including genes related to chemoreception (olfactory and gustation), vision, digestion, detoxification, development, ribosomal and energy metabolism. Chemoreception- and detoxification- and digestion-related genes are stimulated by volatile chemicals and secondary chemicals of different hosts, respectively, which are involved in the regulation of nervous signal transduction that triggers behavioral, physical, and chemical responses to the novel host fruit. Vision-, nerve-, and development-related genes and metabolism-associated genes are activated in response to nonchemical stimuli from different hosts, such as color and phenology, to regulate a comprehensive adaptation of the extending host for tephritids. The chemical and nonchemical signals of hosts activate ribosomal and energy-related genes that result in the basic regulation of many processes of host expansion, including detoxification and development. These genes do not regulate novel host use individually, but multiple genes regulate multilevel adaptation to novel host fruits via multiple mechanisms. These genes may also be potential target genes for RNAi-based control of tephritid pests.